2013
DOI: 10.1002/rem.21364
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Cyclic Ethers by Alkane‐Grown Mycobacterium vaccae JOB5

Abstract: In this study we investigated the cometabolic oxidation of six cyclic ethers by alkane-grownMycobacterium vaccae JOB5. These ethers include, among others, tetrahydrofuran (THF), 1, 1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…may limit its effectiveness as a biomarker, multiple studies have demonstrated the ability of propanotrophs to cometabolize dioxane, supporting the use of this target as a potential biomarker for dioxane biodegradation (20,28,54).…”
Section: Discussionmentioning
confidence: 98%
“…may limit its effectiveness as a biomarker, multiple studies have demonstrated the ability of propanotrophs to cometabolize dioxane, supporting the use of this target as a potential biomarker for dioxane biodegradation (20,28,54).…”
Section: Discussionmentioning
confidence: 98%
“…NBB4 could efficiently degrade chlorinated aliphatic compounds (1,2dichloroethane, vinyl chloride and cis-dichloroethane; Le and Coleman 2011). In turn, Mycobacterium vaccae JOB5 oxidized several cyclic ethers (Lan et al 2013). Vila and Grifoll (2009) documented removal of alkyl-PAHs from the Prestige tanker fuel by Mycobacterium sp.…”
Section: Bacteria Able To Metabolize Both N-alkanes and Aromatic Hydrmentioning
confidence: 99%
“…PG-3-5 greatly enhanced the velocity of butane degradation, demonstrating that the enhanced degradation velocity was the result of the cooperation between the BOB strains and the butanol-oxidizing strain. Since BOB and other hydrocarbon-degrading bacteria play an important role in the elimination of hydrocarbon contamination caused by leaching during petroleum extraction [20,21], our findings about the syntrophic relationships between the alkane and alcohol-oxidizing bacteria might be important for improving the bioremediation efficiency of hydrocarbon contamination.…”
Section: Discussionmentioning
confidence: 92%
“…The bmoX gene encodes the alpha hydroxylase subunit of butane monooxygenase, which is the most conservative gene segment [14,19]. The degradation of other organic pollutants by BOBs has also been studied [20,21].…”
Section: Introductionmentioning
confidence: 99%